POTENTIALS OF BENGKULU’S LOCAL BIOMASS FOR BIOETHANOL PRODUCTION: A SYSTEMATIC LITERATURE REVIEW - Elza Heryensi; Aceng Ruyani; Fitri April Yanti; Rendy Wikrama Wardana; M Lutfi Firdaus (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
The development of bioethanol based on local biomass is an important strategy to support national energy diversification. Still, the potential of Bengkulu biomass and its technical feasibility have not been systematically studied. This study aims to analyze the potential of cassava waste, coconut coir, oil palm empty fruit bunches (OPEFB), and water hyacinth as raw materials for second-generation bioethanol production, and to identify the multidimensional challenges associated with their conversion processes. The method employed is a Systematic Literature Review (SLR) with a qualitative thematic synthesis, based on the PRISMA 2020 guidelines. The search was conducted across five major databases (Scopus, Web of Science, ERIC, IEEE Xplore, and ScienceDirect) with a publication range of 2018-2025, resulting in 414 articles. Twelve articles met the criteria after a quality assessment using MMAT. The results indicate that the utilization of local biomass in Bengkulu remains fragmented. However, there is significant technical potential, including an ethanol yield of 75-180 L/ton of cassava waste, coconut coir through pretreatment with DES/NADES, OPEFB ±10% (v/v) with adaptive yeast, and water hyacinth at 7-8 g/L through SSF. The study offers a multi-feedstock conceptual framework and recommends pilot plants, LCA analyses, and economic studies to support sustainable regional implementation.